Vibrio vulnificus infection in São Paulo, Brazil: case report and literature review - Araujo,Maria Rita Elmor de (2007)
Non cholera Vibrio may cause conjunctivitis, wound infection, gastroenteritis and serious sepsis. Transmission to men is through contact with skin, mucosa or wounds exposed to marine water, and consumption of certain barely cooked or raw seafood, more frequently in the summer. This is one of the first cases of severe infection related to Vibrio vulnificus described in Brazil. The patient was an old man, who ingested seafood in Guarujá, a seashore city near São Paulo, 3 days before hospitalization. He was admitted to the emergency room in an ill state with septic shock. On 2 sets of blood culture a highly virulent microorganism was isolated, Vibrio vulnificus, which leads to sepsis and frequently to death in susceptible patients. The objective of this report was to use this case to discuss clinical aspects, microbiological diagnosis and treatment of the infection caused by this agent, besides the review of epidemiology, associated risk factors and prevention before consuming or getting in contact with seafood, especially in patients with greater susceptibility to this kind of infection.